First species record of Schizogyniidae (Acari: Mesostigmata: Trigynaspida) from Asia - Alireza Nemati; Arsalan Khalili-Moghadam (Persian Journal of Acarology)
In addition to the female genital structures, the most Trigynaspida is diagnosed by the following combination of characters in the adults: presence of eight setae on femora IV, absence of an unpaired postanal seta, presence of the setae av4 and pv4 on tarsi IV, presence of four anterolateral setae (al) on tarsi II–IV, absence of salivary styli in gnathosoma and presence of hypopharyngeal styli in gnathosoma (Kethley 1977; Kim 2004). So far seven species belonging to six trigynaspid families have been reported from Iran: Asternoseiidae, Antennophoridae, Celaenopsidae, Cercomegistidae, Diplogyniidae and Schizogyniidae (Kazemi and Rajaei 2013, Kazemi and Paktinat Saeej 2013, Nemati et al. 2014). The Schizogyniidae Trägårdh, 1950 a poorly known family (Ryke 1957; Kinn 1966; Karg 1977) was recorded for the first time from Palearctic region by Nemati et al. (2014). This family includes only six genera and eleven species (Ryke 1957; Kinn 1966; Trach and Seeman 2014) with the following morphological characters: usually having latigynial plates fused with ventral shield (except in Mixogynium); ventral shield broadest posterior to coxae IV; metasternal shields separate, fused with sternal shield or fused together into a single plate; anal plate free or fused with ventral plate; metapodal plates usually represented by large shields (except in Mixogynium), free or fused with peritremal plate (Kinn 1966; Trach and Seeman 2014).